Impact of AJCC 'T' designation on risk of regional lymph node metastasis in patients with squamous carcinoma of the eyelid. Issue 4 (15th January 2014) - Nasser, Qasiem J; Roth, Katherine G; Warneke, Carla L; Yin, Vivian T; El Sawy, Tarek; Esmaeli, Bita
Abstract : Background/aims: Squamous cell carcinoma (SCC) of eyelid is the second most common cancer of the eyelid with the potential for nodal metastasis. The purpose of this report is to determine whether primary tumour size and 'T' designation in the American Joint Committee on Cancer (AJCC) staging system, 7th edition, correlate with the risk of regional nodal metastasis in patients with eyelid SCC. Methods: Sixty-five consecutive patients with eyelid SCC treated by one ophthalmologist from March 1999 through July 2011 were included in this retrospective cohort study. Disease was staged using the AJCC 7th edition criteria based on clinical, pathological and radiographical data. Main outcome measures included regional lymph node metastasis at presentation, local recurrence, distant metastasis and survival at last follow-up. Results: 40 men and 25 women had a median age of 67.0 years (range 41–89). TNM designations at presentation per the AJCC 7th edition were as follows: T1N0M0, 6 patients; T2aN0M0, 11 patients; T2bN0M0, 17 patients; T2bN1M0, 2 patients; T3aN0M0, 22 patients; T3bN0M0, 2 patients; T3bN1M0, 1 patient; T4N0M0, 3 patients; and T4N1M0, 1 patient. Median follow-up was 27 months (range 1–150). Four patients had nodal metastasis at presentation. Two of these four patients had T2bN1M0 disease, one had T3bN1M0 disease and one had T4N1M0 disease. Two patients, with T3aN0M0 and T4N0M0 tumours, respectively, at presentation, developed lymph node metastasis at 2 weeks and 8.4 months, respectively, after tumour excision. The four patients who had lymph node metastases at presentation and the two who developed lymph node metastases during follow-up had tumours ≥18 mm in greatest dimension or T2b or higher at presentation. Seven local recurrences were observed during follow-up. Two-year and 3-year recurrence-free survival rates were 93% (95% CI 80% to 98%) and 82% (95% CI 63% to 92%), respectively. No distant metastasis or tumour-related death was observed during follow-up. The 2-year and 3-year disease-free survival rates were 90% (95% CI 77% to 96%) and 79% (95% CI 61% to 89%), respectively. Conclusions: Regional nodal metastases were observed among patients who presented with tumours >T2b. Tumour size and the AJCC TNM designations correlate with metastasis and should be reported more often for eyelid SCCs to allow comparisons across centres.